Prinsip Iktikad Baik dalam Perjanjian Asuransi Kesehatan - Haryanti, Nurul Laksmita; , Inayah, S.H, M.H (2017)
This study aims to find an explanation of the implementation of the principle of good faith on the agreement as well as the Health Insurance for mengetaui legal settlement if the insured does not implement the principle of good faith on a treaty Health Insurance. The study uses empirical methods normative approach. The data source of primary data from interviews and additional berumber the form of legislation and regulations, and secondary data obtained from the literature. Data were collected by literature study and field study. And then analyzed using qualitative analysis methods. Research shows that in the implementation of the principle of good faith on the agreement BringinLife and Prudential Insurance in accordance with Article 251 Book of Law Commercial Law. legal settlement if the insured does not implement the principle of good faith on a treaty agreement null and Health Insurance premiums are not paid. Keywords: Agreements, Good faith, Health Insurance